Sustainability accounting: brief history and perspectives - Hyršlová, Jaroslava; Becková, Helena; Kubáňková, Marie (Melandrium, 2015)
Sustainability accounting and reporting are relatively new disciplines that have their early days in the 60s and the 70s of the 20th century. In professional literature these terms have been emerging from the 90s of the last century. An array of research works dealing with various perspectives on these problems has been realised since then. Scientific terminology as well as principles, rules and methods that should be respected and used by the system have been discussed. Sustainability accounting has its roots in financial and managerial accounting, and it is possible to apply it both at macroeconomic (state) and microeconomic (corporate) level. The system provides information for all interested parties in support of decision-making processes in accordance with sustainability principles. The paper deals with sustainability accounting at the corporate level. A brief history of sustainability accounting development is presented and then main benefits and imperfections of the system are discussed. In the paper the main focus is aimed especially at the future development (prospects) of the system. The problems of sustainability accounting are solved from the world development point of view, but the state of solved problems in terms of the Czech Republic is in focus as well.
Účetnictví udržitelného rozvoje: stručná historie a perspektivy
Keywords: sustainability; corporate sustainability; sustainability accounting; sustainability reporting; udržitelnost; podniková udržitelnost; účetnictví udržitelného rozvoje; vykazování udržitelného rozvoje